A Comprehensive Review of Emerging Paradigms in Global Health Research - Aljohani, Yousef Hmdan; alzahrani, Seham Mohammed; Alsharyoufi, Mamdooh Wasel Mohammed; Al-Omari, Abdullah Ghazi; Almrwani, Saleh Hmdan; Alrashidi, Reem Nashmi; Algohny, Amani Farg; Al-Tawri, Nawaf Mustafa (Journal of Ecohumanism, 2024)
International health research has attracted considerable interest in the last decades, mainly attributable to Health inequality, the Emergence of No communicable diseases, and Universal bond industriousness in fighting global health dilemmas. The social transformation of the nature of health problems, on the one hand, and the innovation of disease prevention and control strategies, on the other hand, define the new epistemologies of Global Health on the move. In this paper, these new paradigms are discussed in detail, focusing on the areas of study, the qualification of contexts, and the methods used. To this end, to contribute to the ongoing research in the area, we discuss emerging research themes, gaps, and potential research directions for future work. Through a careful review of scientific literature mixed with methodological approaches, this paper proposes to advance from the current focus on global health subjects to a more rigorous, diverse, and encompassing approach.